Spektralfotometrische Messungen bei 60° Einfallswinkel. (2nd April 2013) - Wilbrandt, Steffen; Böhme, Matthias; Stenzel, Olaf; Schlegel, Ralph; Kaiser, Norbert
<x xml:space="preserve">Abstract</x> Spectrophotometric measurements at 60° incidence angle A measurement VN‐accessory for characterisation and quality control of optical coatings using absolute measurements of transmittance and reflectance for s‐ and p‐polarised light at 60° incidence angle has been developed. In the common case of nearly normal incidence, the polarisation state of the incident light is of low relevance. In the case of 45° incidence angle the Abeles relation holds. Therefore, in both cases, changing the polarisation will add no further information. The use of larger angles, as 60° in our case, is common in ellipsometry. At this large angle of incidence, when measuring thick samples, unwanted effects such as transmission beam offset and further beam splitting caused by multiple internal reflections become significant. Therefore, glass substrates with different thickness have been included into the evaluation process of the 60°‐VN‐accessory. An excellent agreement between theory and measurement could be established for sample thicknesses up to 2.5 mm.